PENGARUH SUPERVISI KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KOMPETENSI PEDAGOGIK GURU DI SMP NEGERI KECAMATAN BANGKO KABUPATEN ROKAN HILIR HILIR - Sudarmiatun, Sudarmiatun; Azhar, Azhar; Burhanud, Dudung (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to analyze the contribution of two independent variables, namely the supervision of the principal and organizational culture, and the dependent variable is the pedagogic competence of teachers at SMPN Bangko District, Rokan Hilir Regency. To obtain the data needed, the writer uses descriptive statistical analysis techniques and inferential analysis. Based on the results of this study, it can be seen that 1) There is an effect of principal supervision on pedagogic competence in SMPN Bangko District, Rokan Hilir Regency. This is evidenced from the results of the t-test that is 3.351 while the t-table is 2.000, thus t-count > ttable (3,351>2,000). 2) There is an influence of organizational culture on the pedagogical competence of teachers at SMPN Bangko District, Rokan Hilir Regency. The results of the calculation of the t test on organizational culture are 3,432 while the t table is 2,000. t count > t table (3,432>2,000). 3) There is a joint influence of principal supervision and organizational culture on the pedagogic competence of teachers at SMPN Bangko District, Rokan Hilir Regency. This is evidenced by Fcount > Ftable or 27.775 > 2.76. The influence of the two variables of supervision and organizational culture on pedagogoic competence is 50.2% while the remaining 49.8% is not discussed in this study.